Retrospective Study Comparing WBC scan and 18F-FDG PET/CT in Patients with Suspected Prosthetic Vascular Graft Infection. (June 2019) - Puges, Mathilde; Bérard, Xavier; Ruiz, Jean-Baptiste; Debordeaux, Frederic; Desclaux, Arnaud; Stecken, Laurent; Pereyre, Sabine; Hocquelet, Arnaud; Bordenave, Laurence; Pinaquy, Jean-Baptiste; Cazanave, Charles
Abstract : Objectives: Prosthetic vascular graft infections (PVGIs) are associated with high mortality rates. To improve treatment outcome, an early and definite diagnosis is critical, and current diagnostic criteria are often insufficient. The accuracy of 2-deoxy-2-[fluorine-18]-fluoro-d -glucose positron emission tomography integrated with computed tomography ( 18 F-FDG PET/CT) and white blood cell (WBC) scan for the diagnosis of PVGI were compared. Methods: A retrospective single centre study was conducted on patients undergoing WBC scan and 18 F-FDG PET/CT for a suspected PVGI between April 2013 and June 2016 at the Bordeaux University Hospital, France. The diagnostic value of both imaging tests was assessed for all grafts, using receiver operating characteristic (ROC) curve analysis. Images were independently interpreted by two nuclear medicine physicians blinded to the patients' clinical and other imaging data. Results: Thirty-nine patients were included, of whom 15 had PVGI. Antibiotic treatment was started before nuclear imaging for 16 patients, including nine patients with a PVGI. The 96 grafts of these patients were analysed, and 19 were infected. The diagnostic value of the WBC scan was significantly higher than 18 F-FDG PET/CT (ROC AUC = 0.902, 95% CI 0.824–0.980, and 0.759, CI 95% (0.659–0.858), respectively, p  = .0071). Interobserver agreement was good for 18 F-FDG PET/CT and excellent for WBC scan (kappa value of 0.76, 95% CI 0.62–0.9, and 0.97, 95% CI 0.92–1, respectively). Only one patient had a false negative 18 F-FDG PET/CT result under antibiotic therapy. Conclusion: The WBC scan has a better diagnostic value than 18 F-FDG PET/CT for PVGI diagnosis.